Utilization of purines or pyrimidines as the sole nitrogen source by Methanococcus vannielii. - DeMoll, E (1986)
Studies of biosynthetic pathways with purines as substrates showed that Methanococcus vannielii was capable of degrading xanthine to an extent that several of the carbon atoms were converted to CO2. Experiments to determine whether this catabolic activity could satisfy the entire nitrogen requirement for growth of M. vannielii showed that urate, guanine, xanthine, or hypoxanthine, but not adenine, could serve as the sole nitrogen source. The pyrimidines uracil and thymine, but not cytosine, were also degraded to serve as a source of nitrogen. Although urate was extensively degraded, it did not replace formate as the sole carbon source for growth of M. vannielii under the conditions imposed.